External Debt and Agricultural Production in Nigeria - Wilson Ebhotemhen; David Umoru (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2019)
Over time, Nigeria has experienced upsurge in external debt stock and several studies have estimated negative impact of growing external debt on economic growth. On sectoral basis therefore, our study proceeds to evaluate such impact of external debt on growth of agricultural production in Nigeria using time series data from 1980 to 2017. For this purpose, we utilized co-integration being test instrument and ECM to investigate link among variables used. The empirical results reveal that external debt failed to yield increase in output returns in agricultural productivity by its inverse association with agricultural output. This indicates that acquired external loans for agriculture within period of study were not optimally utilized for same resolve. Hence, we advise that Nigerian government should demonstrate sound commitment to effective debt management in order to ensure foreign loans are suitably channeled and healthily utilized for purpose acquired for as this would equally guarantee that the output returns would be sufficient for debt service obligation and balance to promote growth in other sectors of Nigerian economy.